The Gross and Biometrical Observations on Femur of the Emu (Dromaius novaehollandiae) - Barvalia, Ishita (Indian Journal of Veterinary Anatomy, 2020)
The carcasses were collected, biologically macerated, cleaned and the bones were completely sundried. The detailed studies of gross anatomy of femur and its biometry have been described. The biometry of the femur included the maximum length and circumference of the diaphysis; the width and thickness of variousstructures at the epiphysis. Dry weight of the bone was also measured in grams (g) and recorded. Various morphological parameters measured are presented in a tabular form.